Human Autologous Serum as a Substitute for Fetal Bovine Serum in Human Schwann Cell Culture - Parisa Goodarzi; Babak Arjmand; Seyed Hassan Emami-Razavi; Masoud Soleimani; Abbas Khodadadi; Fereshteh Mohamadi-Jahani; Hamid Reza Aghayan (Acta Medica Iranica, 2014)
Nowadays, cell -based and tissue engineered products have opened new horizons in treatment of incurable nervous system disorders. The number of studies on the role of Schwann cells (SC) in treating nervous disorders is higher than other cell types. Different protocols have been suggested for isolation and expansion of SC which most of them have used multiple growth factors, mitogens and fetal bovine sera (FBS) in culture medium. Because of potential hazards of animal-derived reagents, this study was designed to evaluate the effect of replacing FBS with human autologous serum (HAS) on SC's yield and culture parameters. Samples from 10 peripheral nerve biopsies were retrieved and processed under aseptic condition. The isolated cells cultured in FBS (1st group) or autologous serum (2nd group). After primary culture the cells were seeded at 10000 cell/cm2 in a 12 wells cell culture plate for each group. At 100% confluency, the cell culture parameters (count, viability, purity and culture duration) of 2 groups were compared using paired t-test. The average donors' age was 35.80 (SD=13.35) and except for 1 sample the others cultured successfully. In first group, the averages of cell purity, viability and culture duration were 97% (SD=1.32), 97/33% (SD=1.22) and 11.77 (SD=2.58) days respectively. This parameters were 97.33% (SD=1.00), 97.55% (SD=1.33) and 10.33 days (SD=1.65) in second group. The difference of cell count, purity and viability were not significant between 2 groups (P>0.05). The cells of second group reached to 100% confluency in shorter period of time (P=0.03). The results of this study showed that autologous serum can be a good substitute for FBS in human SC culture. This can reduce the costs and improve the safety of cell product for clinical application.